2020
DOI: 10.1128/mbio.02975-19
|View full text |Cite
|
Sign up to set email alerts
|

Pangenomics Analysis Reveals Diversification of Enzyme Families and Niche Specialization in Globally Abundant SAR202 Bacteria

Abstract: It has been hypothesized that the abundant heterotrophic ocean bacterioplankton in the SAR202 clade of the phylum Chloroflexi evolved specialized metabolisms for the oxidation of organic compounds that are resistant to microbial degradation via common metabolic pathways. Expansions of paralogous enzymes were reported and implicated in hypothetical metabolism involving monooxygenase and dioxygenase enzymes. In the proposed metabolic schemes, the paralogs serve the purpose of diversifying the range of organic mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
89
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(104 citation statements)
references
References 58 publications
14
89
1
Order By: Relevance
“…3D). The SAR202 group III has been previously shown to be one of the most dominant Chloro exi in the water column of the global deep ocean [17,28], and our result highlights the signi cance of these bacteria in both pelagic and sedimentary habitats of the deep ocean. Expansion of paralogous enzymes, such as avin-dependent monooxygenases, in SAR202 group III has been suggested to be important for their adaptation in different deep-sea habitats, by diversifying the range of organic molecules that the cells can utilize [16,17].…”
Section: Distribution Of the Reconstructed Mags In Hadal Sediments Ansupporting
confidence: 67%
See 1 more Smart Citation
“…3D). The SAR202 group III has been previously shown to be one of the most dominant Chloro exi in the water column of the global deep ocean [17,28], and our result highlights the signi cance of these bacteria in both pelagic and sedimentary habitats of the deep ocean. Expansion of paralogous enzymes, such as avin-dependent monooxygenases, in SAR202 group III has been suggested to be important for their adaptation in different deep-sea habitats, by diversifying the range of organic molecules that the cells can utilize [16,17].…”
Section: Distribution Of the Reconstructed Mags In Hadal Sediments Ansupporting
confidence: 67%
“…Currently, the knowledge on the metabolism of deep-sea Chloro exi mainly relies on metagenomic or single-cell genomic analysis, due to the lacking of cultivated representatives for dominant deep-sea lineages [15][16][17]. These studies revealed that Chloro exi from deep-sea waters harbor genes involved in organosulfur compounds degradation [8,15], sul te oxidation [8,15], and the metabolisms of recalcitrant compounds such as cyclic alkanes and aromatic compounds [15][16][17]. The analysis of deep-sea Chloro exi from anoxic subsea oor sediments suggest these bacteria have potential for reductive respiration of organohalogen compounds, and for the fermentation of OM combined with CO 2 xation via the Wood-Ljungdahl pathway [9,18].…”
Section: Introductionmentioning
confidence: 99%
“… 2017 ; Saw et al . 2020 ), peptidases (Mehrshad et al . 2018 ) and potentially haloalkane and haloacetate dehalogenases (Wasmund et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a sister clade to the Anaerolineae named WPS-2 (formerly 'subphylum I') contains strains that encode phototrophic machinery but lack carbon fixation machinery (Ward et al, 2019a, b). The non-phototrophic Chloroflexi comprise a larger proportion of the phylum, predominately in the class Anaerolineae that are are widespread in the environment, including strains recovered from activated sludge and wastewater (Nierychlo et al, 2019) and several metagenome assembled genomes from deep ocean environments (Saw et al, 2020), but the ecology of the class remains poorly understood in hot springs.…”
Section: Introductionmentioning
confidence: 99%